Do stay-at-home orders cause people to stay at home? Effects of stay-at-home orders on consumer behavior - Diane Alexander; Ezra Karger (Federal Reserve Bank of Chicago, 2020)
We link the county-level rollout of stay-at-home orders to anonymized cellphone records and consumer spending data. We document three patterns. First, stay-at-home orders caused people to stay at home: county-level measures of mobility declined by between 9% and 13% by the day after the stay-at-home order went into effect. Second, stay-at-home orders caused large reductions in spending in sectors associated with mobility: restaurants and retail stores. However, food delivery sharply increased after orders went into effect. Third, there is substantial county-level heterogeneity in consumer behavior in the days leading up to a stay-at-home order.
Keywords: 330; Konsumentenverhalten; Mobilität; Politische Partei; Coronavirus; Gesundheitspolitik; USA